2014
DOI: 10.1007/s00405-013-2845-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of cold ablation (coblation) in the treatment of tonsillar hypertrophy of the tongue base

Abstract: The treatment of diseases of the lingual tonsils is still under debate, and surgical interventions are often associated with significant morbidity and complications. The aim of the present study was to evaluate the safety of lingual tonsillectomy using cold ablation (coblation) as a new treatment of lingual tonsil diseases. In this retrospective, bicentric study, we included all patients between 2005 and 2012 who underwent cold ablation (Coblation(®)) of the lingual tonsils. We assessed the frequency of postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Coblation assisted lingual thyroid and lingual tonsil resection techniques were used and successful results were reported [ 13 15 ]. Leitzbach et al [ 14 ] reported successful results and low complication rates in 108 patients undergoing coblation assisted resection due to tongue root and lingual tonsil hypertrophy. However, transoral resection techniques have limited point of view and lead to difficulty in resection owing to difficulty in manipulation, which restricts their use [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coblation assisted lingual thyroid and lingual tonsil resection techniques were used and successful results were reported [ 13 15 ]. Leitzbach et al [ 14 ] reported successful results and low complication rates in 108 patients undergoing coblation assisted resection due to tongue root and lingual tonsil hypertrophy. However, transoral resection techniques have limited point of view and lead to difficulty in resection owing to difficulty in manipulation, which restricts their use [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] It is noteworthy that procedures involving partial resection of the tongue base, in addition to the removal of lingual tonsils, tend to carry high morbidity with possible complications such as bleeding, hypoglossal nerve paralysis, risk of airway compromise, and infections, such as lingual or submental abscess. 7 The purpose of this study was to review the patients at our institute who have had lingual tonsil surgery for various indications. We also aimed to revisit the techniques used and their outcome.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Other more infrequently described symptoms are sore throat, lethargy, change of speech, and choking on food. 7 To evaluate possible LTH, endoscopic examination, magnetic resonance imaging (MRI), and computed tomographic imaging have been used. 2 The grading systems used to assess the LTH have been inconsistent, making the interpretation of different studies challenging.…”
Section: Introductionmentioning
confidence: 99%
“…New energy instruments such as harmonic scalpel, LigaSure, coblation and plasma knife are increasingly being used during surgical procedures. Their safety and efficacy are well documented in the literature . The LigaSure vessel sealing system was reported to shorten the operative duration in patients receiving superficial parotidectomy when compared with the conventional method .…”
mentioning
confidence: 99%